Assessment of the Health Status of Mussels Mytilus galloprovincialis Along the Campania Coastal Areas: A Multidisciplinary Approach - Carella, Francesca; Aceto, Serena; Mangoni, Olga; Mollica, Maria Pina; Cavaliere, Gina; Trinchese, Giovanna; Aniello, Francesco; De Vico, Gionata (Frontiers in Physiology, 2018)
The bivalve Mytilus galloprovincialis has a broad geographic distribution, represent an important species for the ecology of coastal waters, also constituting a major aquaculture species. In the present work, molecular and tissue biomarkers were examined in mussel populations (M. galloprovincialis) located in four different areas of the coastal water of the Campania Region. During an annual life cycle, we analyzed the expression patterns of several genes commonly used to estimate cellular stress response and damage, namely p53, p63, HSP70, MT-10, and MT-20, related tissue lesions (pathogens, inflammations, digestive tubules damage), oxidative stress indicators (H2O2, SOD specific activity) and associated environmental data. The computed Principal Component Analysis showed that the areas were discernible based on the environmental data and biomarker results. About animal health status, mussels from Gulf of Pozzuoli and Naples’s harbor did show a thinnest epithelial cell of digestive tubules compared to mussels sampled from other sampling sites; moreover, high prevalence of cases of intersex in three of the examinated areas were observed. The presence of a potential zoonotic pathogen (Nocardia crassostreae) was identified, appearing as an important possible emerging disease. We also reported the OIE notifiable protozoa Marteilia refringens in three areas out of four. The likely impact of both observed pathogens on the mussel health and shellfish aquaculture needs to be urgently addressed. Results are discussed considering animal histopathological health parameters and biological effects.